Chronic Encapsulated Expanding Hematomas After Stereotactic Radiosurgery for Intracranial Arteriovenous Malformations: An International Multicenter Case Series. Issue 1 (25th January 2023) - Abou-Al-Shaar, Hussam; Patel, Aneek; Mallela, Arka N.; Bin-Alamer, Othman; Niranjan, Ajay; Peker, Selcuk; Samanci, Yavuz; Liscak, Roman; May, Jaromir; Kumar, Jeyan Sathia; Sheehan, Jason P.; Lunsford, L. Dade
Abstract : BACKGROUND: Stereotactic radiosurgery (SRS) offers a minimally invasive treatment modality for appropriately selected intracranial arteriovenous malformations (AVMs). Recent reports have described the development of rare, delayed chronic encapsulated expanding hematomas (CEEHs) at the site of an angiographically confirmed obliterated AVM. OBJECTIVE: To elucidate the incidence, characteristics, and management of CEEH in patients with AVM after SRS. METHODS: The records of all patients who underwent SRS for an intracranial AVM at 4 institutions participating in the International Radiosurgery Research Foundation between 1987 and 2021 were retrospectively reviewed. Data regarding characteristics of the AVM, SRS treatment parameters, CEEH presentation, management, and outcomes were collected and analyzed. RESULTS: Among 5430 patients, 15 developed a CEEH at a crude incidence of 0.28%. Nine patients were female, and the mean age was 43 ± 14.6 years. Nine patients underwent surgical evacuation, while 6 were managed conservatively. The median CEEH development latency was 106 months after SRS. The patients were followed for a median of 32 months, and 9 patients improved clinically, while 6 patients remained stable. No intraoperative complications were reported after CEEH resection, although 1 patient recovered from postoperative meningitis requiring intravenous antibiotics. CONCLUSION: CEEH is a rare, late complication of AVM SRS with an incidence of 0.28% and a median latency of 106 months. In the presence of a delayed and symptomatic expanding hematoma in the bed of an angiographically obliterated AVM, surgical resection resulted in clinical improvement in most patients. Conservative management is possible in asymptomatic patients with stable, small-sized hematomas in deeply seated locations.